Predicting First Year University Students' Academic Success - Aboma Olani (Electronic Journal of Research in Educational Psychology, 2009)
Introduction: Premature withdrawal from university due to academic failure can present problems for students, families and educators. In an effort to widen the understanding regarding factors predicting academic success in higher institutions, prior academic achievement measures (preparatory school grade average point (GPA), aptitude test scores, and university entrance exam scores) and psychological variables (achievement motivation and academic self-efficacy) were examined to predict first year university students' GPA. Method: Prior academic achievement records of 3301 first year university students were obtained from archival sources. From these, 214 students also filled in a self-report that gathered information concerning psychological variables. The data were analyzed using standard multiple regression analysis in order to explain the degree to which the GPA scores of first year university students were predicted from their prior academic achievements and psychological behaviors. Stepwise multiple regression analysis was employed to identify relatively the most important predictors of university GPA. Results The result revealed that prior academic achievement measures and psychological variables in combination accounted for 17% of the variance in students' university GPA scores. The sole contribution of psychological variables was 4 %. Relatively a higher percentage of variance accounted for was found for females (34%) than males (15%). Further, preparatory school GPA was found to be the only independent significant predictor of university GPA for both sexes. Conclusion: The results of this study support the conclusion that students' pre-college academic performances are strong predictors of GPA at university level. The effects of psychological variables on university GPA are also not negligible. Based on the findings of the study, practical implications for student support services and admissions at university and implications for research are presented.